2010
DOI: 10.1016/j.icarus.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Titan’s atomic hydrogen corona

Abstract: Based on measurements performed by the Hydrogen Deuterium Absorption Cell (HDAC) aboard the Cassini orbiter, Titan's atomic hydrogen exosphere is investigated. Data obtained during the T9 encounter are used to infer the distribution of atomic hydrogen throughout Titan's exosphere, as well as the exospheric temperature.The measurements performed during the flyby are modeled by performing Monte Carlo radiative transfer calculations of solar Lyman-α radiation, which * Corresponding author, Tel. +33 557 776 127 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…For illustrative purpose, the best-fit corona models for T83 are given by the red lines in Figure 1(c), with an inferred exobase temperature of 177K for N 2 and 159K for CH 4 , respectively. The same approach has also been used in previous analyses of Titan's H 2 corona (Cui et al , 2011, atomic H corona (Hedelt et al 2010), as well as N 2 and CH 4 coronae (De La Haye et al 2007a).…”
Section: Characterization Of Titan's N 2 and Ch 4 Coronaementioning
confidence: 99%
See 1 more Smart Citation
“…For illustrative purpose, the best-fit corona models for T83 are given by the red lines in Figure 1(c), with an inferred exobase temperature of 177K for N 2 and 159K for CH 4 , respectively. The same approach has also been used in previous analyses of Titan's H 2 corona (Cui et al , 2011, atomic H corona (Hedelt et al 2010), as well as N 2 and CH 4 coronae (De La Haye et al 2007a).…”
Section: Characterization Of Titan's N 2 and Ch 4 Coronaementioning
confidence: 99%
“…De La Haye et al (2007b) later evaluated the role of exothermic ion-neutral chemistry, but found it inadequate to produce the suprathermal N 2 and CH 4 populations. In addition, the atomic H corona on Titan was sampled by the Cassini Hydrogen Deuterium Absorption Cell (HDAC) instrument, and existing studies using the HDAC data did not support the presence of a hot atomic H population (Hedelt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Two main instruments on board Cassini have been able to investigate the Titan thermosphere and exosphere: the Ultraviolet Imaging Spectrograph (UVIS) (Esposito et al 2004;Hedelt et al 2010) and the Ion and Neutral Mass Spectrometer (INMS) (Waite et al 2004). Cassini also has the capability of detecting in situ high energy plasma particles using the Magnetospheric Imaging Instrument (MIMI).…”
Section: Description Of the Cassini Experimentsmentioning
confidence: 99%
“…Its Hill sphere radius (Hill 1878), which gives the limit of its gravitational influence and thus a good estimation for the upper limit of its exosphere, is about 50,000 km. As a consequence, the measurements available today (up to 2000 km altitude, for an exobase around 1400-1500 km) are only able to provide information in the lower part of the corona, except for molecular hydrogen with observations up to 7000 km altitude or atomic hydrogen with the UVIS experiment (Hedelt et al 2010).…”
Section: Titan Exospherementioning
confidence: 99%
See 1 more Smart Citation